Polysulfone/Cellulose Acetate Phthalate/Polyvinylpyrrolidone (PSf/CAP/PVP) Blend Membranes: Effect of Evaporation Time on Blend Membrane Characteristics - Asmadi, Ali; Rosli, Mohd Yunus; Mohamad, Awang; Sofiah, Hamzah; Mohammad Hakim, Che Harun; Fazureen, Azaman; Muhammad Abbas, Ahmad Zaini (Springer Champ, 2022)
Recently, researchers proved that the evaporation time during the membrane fabrication process has a significant effect on the characteristics and performance of membranes. In this study, flat sheet asymmetric polysulfone/cellulose acetate phthalate/polyvinylpyrrolidone (PSf/CAP/PVP) blend membranes were fabricated at different evaporation time in the range of 0–20 s to investigate the effect of the evaporation time on characteristics of the blend membranes. The PSf/CAP/PVP blend membranes were characterized in terms of water content, porosity, pure water flux and permeability coefficient. The results showed that an increase of evaporation time from 0 to 20 s has resulted in decreasing of water content and porosity of the PSf/CAP/PVP blend membranes. The permeation water flux of the blend membrane was decreased with the increment of evaporation time. This indicated that an increase of evaporation time would lead to a decrease of the membrane permeability coefficient and hence increased the membrane resistance to permeation of water through the membranes.